Association between serum autotaxin or phosphatidylserine‐specific phospholipase A1 levels and melanoma - Kurano, Makoto; Miyagaki, Tomomitsu; Miyagawa, Takuya; Igarashi, Koji; Shimamoto, Satoshi; Ikeda, Hitoshi; Aoki, Junken; Sato, Shinichi; Yatomi, Yutaka (Journal of dermatology, 2018)
Autotaxin (ATX), a producing enzyme for lysophosphatidic acids, was first identified from the medium of a melanoma cell line and has been considered to be one of the candidate targets to treat melanoma; however, the association between serum ATX and melanoma in human subjects has not been elucidated. Along with ATX, phosphatidylserine‐specific phospholipase A1 (PS‐PLA1) is a producing enzyme for lysophosphatidylserine, a similar glycero‐lysophospholipid mediator to lysophosphatidic acids. In the present study, we aimed to investigate the association between serum ATX or PS‐PLA1 levels and melanoma. We measured the serum levels of ATX, ATX isoforms and PS‐PLA1 in subjects with melanoma (n = 57) and healthy subjects (n = 58). We further investigated the existence of trends according to the clinical stages of melanoma. We observed that serum total ATX and classical ATX levels were significant higher and serum novel ATX levels tended to be higher in male subjects with melanoma, while no significant difference was observed between the two groups in female subjects. The trend test revealed that the serum total ATX and ATX isoforms were significantly associated with the clinical stages of female subjects with melanoma. Regarding PS‐PLA1, serum PS‐PLA1 levels were significantly higher in the melanoma subjects and associated with the clinical stages. The present study is the first study which revealed the association between ATX or PS‐PLA1 and melanoma, suggesting the possible involvement of ATX/lysophosphatidic acids or PS‐PLA1/lysophosphatidylserine axis in the pathogenesis of melanoma.